Blink Reflex R2 Amplitudes in Cervicogenic Headache, Chronic Tension-Type Headache and Migraine - Sand, T; Møll-Nilsen, B; Zwart, A J (Cephalalgia, 2006)
Blink reflex R2 amplitude was investigated in seven patients with cervicogenic headache (CEH), 12 patients with chronic tension-type headache, 23 patients with migraine (10 with aura) and 17 headache-free controls. Standard electrical stimulation of the supraorbital nerve was applied and the response was recorded from the ipsilateral and the contralateral orbicularis oculi muscles. Low R2 amplitude was found in CEH patients compared with control subjects. Headache is unilateral in CEH and the ipsilateral and contralateral responses after stimulation on the painful side were most depressed. R2 amplitude was not significantly affected in migraine and tension headache patients. The results suggest that lower brainstem excitability is reduced in CEH. A state of hypoactivity may be present in caudal trigeminal nucleus neurons on the symptomatic side.